Show that 2sin(x) =(4cos(x)-1)/tan(x) can be written as: 6cos^2(x)-cos(x)-2=0

Rearranging gives:4cos(x)-1 = 2sin(x)tan(x) Substituting in tan(x)=sin(x)/cos(x) gives:4cos(x)-1 = 2sin(x)(sin(x)/cos(x))2sin2(x)=4cos2(x)-4cos(x)Substituting in 2sin2(x) = 2-2cos2(x) (from the trigonometric identity: sin2(x) = 1-cos2(x))2-2cos2(x)=4cos2(x)-4cos(x)Rearranging this by collecting like terms gives:6cos2(x)-cos(x)-2=0

Answered by Olivia T. Maths tutor

15275 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Factorise 6x^2 + 7x - 3=0


what does 'differentiation' mean?


Does the equation x^2 + 2x + 5 = 0 have any real roots?


If y = 2^x, find dy/dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences